Pengaturan Tindak Pidana Cyberbullying di Indonesia - Octaviana Dewi, Imas (Universitas Ekasakti, 2023)
One of the crimes that occur in cyberspace which is a current problem is cyberbullying. Cyberbullying is a form of intimidation that uses information and communication technology for deliberate purposes, carried out continuously, with the aim of harming other people by intimidating, threatening, hurting/insulting other people's self-esteem, to cause hostility by an individual or group. This research is normative legal research which aims to analyze the concepts and regulations regarding cyberbullying and criminal acts in Indonesia. The results of this research are in article 27 paragraph (3) of the ITE Law which states that every person intentionally and without right distributes and/or transmits and/or makes accessible Electronic Information and/or Electronic Documents which contain insulting and/or defamatory content. Good. Then in article 27 paragraph (4) which states that every person intentionally and without right distributes and/or transmits and/or makes accessible Electronic Information and/or Electronic Documents which contain extortion and/or threats.